Knowledge, attitude and practice towards tuberculosis among community of Kulim municipal council, Kedah, Malaysia - Mohd Salleh, Syahrul Farhanah; A.Rahman, Nor Azlina; A.Rahman, Nor Iza; Haque, Mainul (Japan International Cultural Exchange Foundation, 2018)
Aims: This study investigated knowledge, attitude and practice towards tuberculosis (TB) among the community in Kulim Municipal Council, Kedah, Malaysia. Its associated factors and the correlation between the knowledge, attitude and practice were also studied. Methodology: A cross-sectional study using self-administered questionnaire had been carried out among the community in Kulim Municipal Council, Kedah involving 102 respondents using convenient sampling. Descriptive statistics, correlation, Independent t-test and Anova were used to analyze the data accordingly. Results: It was found that the respondents had moderate knowledge (mean score = 85.54 ± 16.911) and practice (mean score = 7.37 ± 1.955) but poor attitude (mean score = 51.80 ± 10.833) towards TB and TB patients. Besides, there was no significant relationship found between knowledge, attitude and practice towards TB infection among the community in Kulim Municipal Council, neither significant factors associated with the knowledge, attitude and practice. Conclusion: The findings of this study are expected to build awareness of this community towards TB, thus assisting in planning the effective methods to promote better knowledge and understanding, and removing the misconceptions regarding TB infection among the community and consequently reducing the prevalence of TB and improving the community's health quality.